Teachers’ perceptions and aspirations for development of International Mindedness: A case study of one International Baccalaureate school in Kazakhstan - Rybkin, Vladimir (Nazarbayev University Graduate School of Education, 2020)
The idea of global education has become more popular over the last several decades. One of the world's educational networks serving in its cultivation is the organization of International Baccalaureate (IB). One of the core elements of its program is the concept of international mindedness (IM), described as “promoting of intercultural awareness, international understanding, and world peace” (Belal, 2015, p. 19). This study sought to examine how teachers of one Kazakhstani IB school understand the concept of IM as well as their willingness and preparedness to help develop this concept in their students. The research question guiding this study was: How do the teachers of an IB school in Kazakhstan perceive and develop IM in their students? The objective nature of IM has an impact on the epistemological approach of the researcher, namely the postpositivist paradigm, and, consequently, necessitated the use of an exploratory sequential mixed method design. The results of the study have demonstrated that many of the participants (1) know about the importance of IM, although they have no clear vision of what IM is , and what are its key elements; (2) use different methods for the promotion of the concept in their lessons; (3) acknowledge the role of IB programs in the cultivation of IM; (4) consider it as a possible threat to the maintenance of the students’ cultural and national identity. The main recommendations of this research are (1) for administrators, to engage teachers in defining the concept of IM for their school; (2) for teachers, they should be aware of what IM is, and its orientation to the respect of different cultures; (3) for IB, to define IM more clearly and for them to be informed that this study supported the vision of other researchers (Poonoosamy, 2016, 2018) who recognized the tensions in the promotion of the concept of IM with a problem of a resurgence of national and cultural identity.
Keywords: International Baccalaureate; International mindedness; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education